2022
DOI: 10.3390/genes13060957
|View full text |Cite
|
Sign up to set email alerts
|

A Logical Framework for Forensic DNA Interpretation

Abstract: The forensic community has devoted much effort over the last decades to the development of a logical framework for forensic interpretation, which is essential for the safe administration of justice. We review the research and guidelines that have been published and provide examples of how to implement them in casework. After a discussion on uncertainty in the criminal trial and the roles that the DNA scientist may take, we present the principles of interpretation for evaluative reporting. We show how their app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Due to the complexity of DNA-TPPR issues and its impact on activity-based touch DNA evidence evaluation, some members of the forensic community hold the opinion that trained DNA scientists should provide guidance to the legal system, when the point of contention is not who the DNA belongs to but how it got there [12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…Due to the complexity of DNA-TPPR issues and its impact on activity-based touch DNA evidence evaluation, some members of the forensic community hold the opinion that trained DNA scientists should provide guidance to the legal system, when the point of contention is not who the DNA belongs to but how it got there [12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…The underutilization of the DNA services may be due to the fact that at that time 'neither of the 6 forensic DNA laboratories in Bangkok is accredited for forensic DNA analysis by international accreditation bodies nor ISO 17025:2005' although the personnel had positive attitude towards quality assurance standards and accreditations. Another important aspect that may influence the usability of DNA evidence is the ability of forensic scientists to communicate the scientific findings through expert reports and testimonies in the court of law, considering the differences in education, backgrounds, languages and expectations of legal personnel and police investigators [186]. In this regard, Mousseau et al [187] reported the narrow view on forensic science and its potential among senior police officers in Quebec, Canada, and suggested that closer connections must be bridged among forensic science, policing and security.…”
Section: Knowledge Perception and Readiness Of Forensic And Legal Pra...mentioning
confidence: 99%
“…The viability of the discipline is assured by guarantees that the forensic genetics techniques are valid: they ‘work’ and can be operationalised (although effectiveness, while central to integrity, requires specific focus due to its vital part in helping to legitimise the role for forensic genetics in society). Data gathered and produced must be reliable and universally understandable without complex translation or interpretation that could lead to confusion and variability (e.g., efforts have been made around evaluative reporting [ 45 , 46 ]). Systems and processes should be guaranteed (as far as possible) by robust quality assurance mechanisms aligned with internationally agreed standards.…”
Section: Integritymentioning
confidence: 99%